The need for changes in travel behaviour towards a low carbon society - Sinniah, Gobi Krishna (2013)
Travel behaviour studies were the key issues of analysis in transportation sector in the 1950s and 1960s, especially regarding on travel behaviour and spatial interaction.Travel behaviour trends have increased drastically all over the world. With the present reality of climate change, the transportation studies are becoming increasingly important, in regards of travel behaviour changes. It is important to understand the needs to change travel behaviour as one of the initiative to achieve sustainable transportation. In achieving transportation sustainability, understanding on travel behaviour and needs can be more functional and useful for transportation planners to encourage people to use public transportations. In recent years, Low Carbon Society (LCS) concept has taken place to change the people lifestyles, especially to increase the use of public transportations. Undeniably, the only solution to a more sustainable transportation leading to a low carbon society is through a higher adoption rate of public transportation. However, it is still far to achieve as far as transportation planners is concerned because of the lack of understanding on the social needs to complement with public transportations. The planning of the fast developing region of Iskandar Malaysia, which is one of the major economic growth conurbation located in southern part of Peninsular Malaysia, provides a good opportunity to transportation planners or engineers to incorporate the ideas of low carbon society into designing a sustainable transportation systems. Thus, this paper aims to discuss the issues and potential implementation of the ideas to change the travel behaviour of people. This paper also provides current findings of transportation studies on the ongoing research to achieve a low carbon society in Iskandar Malaysia.